ChemInform Abstract: Synthesis of Furans and Pyrroles from 2‐Alkoxy‐2, 3‐dihydrofurans Through a Nucleophilic Substitution‐Triggered Heteroaromatization. Issue 31 (14th July 2016) - Liu, Changhui; Zhou, Li; Huang, Wenbo; Wang, Man; Gu, Yanlong
Abstract: 2‐Butoxy‐substituted‐2, 3‐dihydrofurans and a variety of carbon nucleophiles offer a diverse synthesis of furans, pyrroles, and dihydrothiophenes in the presence of a Cu‐ or Fe‐catalyst.